1983
DOI: 10.1080/00288233.1983.10427060
|View full text |Cite
|
Sign up to set email alerts
|

Boron deficiency and response in white and red clovers and lucerne

Abstract: White clover (Trifolium repens L.), red clover (Trifolium pratense L.), and lucerne (Medicago sativa L.) were grown in the glasshouse on a soil known to be low in available boron (B). 6 rates of B and 3 rates of lime in factorial combination were applied. B deficiency symptoms developed in all 3 species and these are described. Dry matter responses to B were greater for red clover and lucerne than for white clover. Critical B concentration ranges in plant material of 13-16, 15-18, and 17-18 ppm were establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…Less than 57o of the total soil B is available for crop uptake (Gupta 1968) (Miljkovic et al 19661' Werkhoven 1964;Whitestone et al 19421, Kanwar and Singh 196l (Sherrell 1983), Sweden (Eriksson 19'79), Nigeria (Singh and Balasubramanian 1983), and England (Wallace 1951). Boron deficiency has also been found in some arid regions of India (Garg et al 1979;Gulati et al I 980) and Pakistan (Khan et al 1979).…”
Section: Sources Of Boron In the Environmentmentioning
confidence: 99%
“…Less than 57o of the total soil B is available for crop uptake (Gupta 1968) (Miljkovic et al 19661' Werkhoven 1964;Whitestone et al 19421, Kanwar and Singh 196l (Sherrell 1983), Sweden (Eriksson 19'79), Nigeria (Singh and Balasubramanian 1983), and England (Wallace 1951). Boron deficiency has also been found in some arid regions of India (Garg et al 1979;Gulati et al I 980) and Pakistan (Khan et al 1979).…”
Section: Sources Of Boron In the Environmentmentioning
confidence: 99%
“…The B analyses of red and white clover from all three trials showed sufficient B concentrations in the -B plots, i.e. >20 mg kg -1 DM ( Sherrell 1983a). Grass B concentrations were at the lower limit of the normal range (3 mg kg -1 DM) (Sherrell 1983b) (Fig.…”
Section: Effects Of B Fertilisation On Dry Matter Yield and Soil And mentioning
confidence: 99%
“…The forages at Rådde were vigorous, with a high percentage of red clover and yield around 400 kg ha -1 above the average level for the area (2920 kg ha -1 for first-year ley, 2 nd cut), while the swards at Borrarp+S and Borrarp-S were weak, with low red clover content and yields of 1000 and 1300 kg ha -1 , respectively, below the average for the area (Jansson 2008) (Table 1). In grass-legume crops it is not common to see yield losses due to B deficiency during vegetative growth (Sherrell 1983a). In a greenhouse study, B concentrations for yield response to B fertilisation were determined in red clover (15-18 mg B kg ) and symptoms of B deficiency were observed (Sherrell 1983a).…”
Section: Effects Of B Fertilisation On Dry Matter Yield and Soil And mentioning
confidence: 99%
See 1 more Smart Citation
“…De verstoorde ontwikkeling van wortelknolletjes geeft een lagere N-binding en leidt tot het afsterven van celweefsel. In een potproef met een bemestingstrap oplopend van 0,11 tot 3,6 kg B ha -1 vond Sherrell (1983a) Kinsela 2011). Het Co-gehalte in witte klaver kan bij een lage Co-opname hoger zijn dan in Engels raaigras, maar bij een hoge opname juist lager (Sherell 1990).…”
Section: Boriumunclassified